2021
DOI: 10.3389/fcimb.2021.673465
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Salivary Mycobiome in a Cohort of Oral Squamous Cell Carcinoma Patients From Sudan Identifies Higher Salivary Carriage of Malassezia as an Independent and Favorable Predictor of Overall Survival

Abstract: BackgroundMicrobial dysbiosis and microbiome-induced inflammation have emerged as important factors in oral squamous cell carcinoma (OSCC) tumorigenesis during the last two decades. However, the “rare biosphere” of the oral microbiome, including fungi, has been sparsely investigated. This study aimed to characterize the salivary mycobiome in a prospective Sudanese cohort of OSCC patients and to explore patterns of diversities associated with overall survival (OS).Materials and MethodsUnstimulated saliva sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 84 publications
0
50
0
Order By: Relevance
“…Finally, findings from a recent mechanistic study in pancreatic cancer showed that mycobiota with predominance of the Malassezia genus displayed tumor‐promoting effects through activation of mannose‐binding lectin which binds to the glycans of the fungal wall with subsequent involvement of adaptive responses (i.e., upregulation of the C3 complement cascade which was proved necessary for tumor development in this model) 40 . Interestingly, upregulation of the same genus in cases of OSCC was shown to correlate with favorable prognosis, highlighting the organ‐specific pathogenicity of mycobiome dysbiosis 41 …”
Section: The Oral Mycobiome As An Initiator Of Oral Carcinogenesismentioning
confidence: 75%
See 2 more Smart Citations
“…Finally, findings from a recent mechanistic study in pancreatic cancer showed that mycobiota with predominance of the Malassezia genus displayed tumor‐promoting effects through activation of mannose‐binding lectin which binds to the glycans of the fungal wall with subsequent involvement of adaptive responses (i.e., upregulation of the C3 complement cascade which was proved necessary for tumor development in this model) 40 . Interestingly, upregulation of the same genus in cases of OSCC was shown to correlate with favorable prognosis, highlighting the organ‐specific pathogenicity of mycobiome dysbiosis 41 …”
Section: The Oral Mycobiome As An Initiator Of Oral Carcinogenesismentioning
confidence: 75%
“…40 Interestingly, upregulation of the same genus in cases of OSCC was shown to correlate with favorable prognosis, highlighting the organ-specific pathogenicity of mycobiome dysbiosis. 41 In this pathogenic model, an environmental factor (Candida) causes well-established hyperplastic changes in the lining epithelium of the oral mucosa termed chronic hyperplastic candidosis (CHC) with the potential of progressing to a premalignant (OED) and malignant (OSCC) sequence through the previously described mechanisms (Figure 1A). It is obvious that intervention with antifungal therapy in the reversible step of CHC may result in regression of the clinically identifiable white plaque and thus preclude the development of cancer, 42 while intervention after the development of OED does not result in regression of the established dysplastic and molecular changes but may eliminate any further tumor-initiating effects of Candida.…”
Section: The Oral Mycobiome As An Initiator Of Oral Carcinogenesismentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, they have demonstrated that repopulation with Malassezia could promote PC through mannose-binding lectin (MBL) signal pathway, thus accordingly its ablation with amphotericin B in murine models was found to slow oncogenic progression (31,105). Malassezia also showed higher relative abundance in patients with oral squamous cell carcinoma (OSCC), compared with control volunteers (106). In addition, Gao and collaborators discovered that although there was no significant difference in stool mycobiota diversity between CRC patients and healthy controls, the fungal subgroup Malassezia genus was more enriched in people with CRC, which was positively correlated with tumor progression (48).…”
Section: Malassezia Is Associated With Cancermentioning
confidence: 99%
“…Neoplastic processes affecting other organs have been investigated [ 10 ], including pancreatic cancer induced by Malassezia genus [ 11 ]. However, conversely, the same fungus was shown to correlate with favorable prognosis [ 12 ] in oral cancer, highlighting the complex and organ-specific oncogenicity of mycobiome dysbiosis. Within the framework of oral cancer, C .…”
Section: Introductionmentioning
confidence: 99%